The role of employment interruptions and part-time work for the rise in wage inequality - Martin Biewen; Bernd Fitzenberger; Jakob de Lazzer (IZA Journal of Labor Economics, 2018)
The incidence of employment interruptions and temporary part-time work has grown strongly among full-time workers, yet little is known about the impact on wage inequality. This is the first study showing that such episodes play a substantial role for the rise in inequality of full-time wages, considering the case of Germany. While there are also strong composition effects of education for males and of age and experience for females, changes in industry and occupation explain fairly little of the inequality rise. Extending the analysis to total employment reveals substantial negative selection into part-time work.
Keywords: J31; J20; J60; 330; Wage inequality; Part-time employment; Employment interruptions; Composition effects